Red sorghum (Sorghum bicolor) leaf sheaths as source stable pigments - Oscar Zannou; Yann Emmanuel Miassi; Kossivi Fabrice Dossa; Marcel Houngbédji; Oyeniran Bernadin Agani; Yénoukounmè E. Kpoclou; D. Sylvain Dabadé; Midimahu Vahid Aïssi; Ilkay Koca; Adéchola P. P. Kayodé; Charis M. Galanakis (Discover Food)
Abstract Pigments are widely valued as colorants or bioactive agents in food, pharmaceutical, and cosmetic sectors. The increasing attention on the natural pigments can be associated with the availability, dietary, low-cost, bioactivity and safety. Sorghum bicolor is a common plant crop with many health benefits commonly. 3-deoxyanthocyanidin derivatives are the predominant anthocyanidins in the leaf sheaths of red sorghum. In this review, the phytochemical and nutritional properties of the leaf sheaths of red sorghum and the stability of the main pigments are discussed. In addition, the taxonomical and geographic distribution and traditional uses of the red sorghum are discussed. Anthocyanidins (luteolinidin, apigeninidin, apigeninidin-flavene dimer, apigeninidin-7-o-methylflavene dimer and 7-o-methylapigeninidin) as well as other flavonoids, phenolic acids, alkaloids, saponins, steroids and tannins have been reported as dominant phytochemicals in the leaf sheaths of red sorghum. They are rich source of micronutrients like essential vitamins and minerals. These properties attract populations to use the leaf sheaths of red sorghum for diverse purposes. It is also resulted that 3-deoxyanthocyanidins in the leaf sheaths of red sorghum are resistant to pH, temperature, light and copigments.